Retargeting Higher Education Access and Persistence Efforts: Illustrating a 'System' Focused Process for Improving Public Policy - Hansen, W. Lee; Stampen, Jacob (My University, 1999)
This paper illustrates a "systems" approach, based on the quality function deployment model, to examine both the direct and interaction effects of multiple solutions aimed at improving access and persistence.